2015
DOI: 10.7439/ijasr.v1i3.1915
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ciprofloxacin Hydrochloride in Bulk and Formulation by Derivative UV-Spectrophotometric Methods

Abstract: Simple, fast and reliable spectrophotometric methods were developed for determination of Ciprofloxacin Hydrochloride in bulk and pharmaceutical dosage forms. The solutions of standard and the sample were prepared in Distilled Water. The quantitative determination of the drug was carried out using the zero/0 th , first, and second order method values measured at264, 273and 273 nm respectively. Calibration graphs constructed at their wavelengths of determination were linear in the concentration range of Ciproflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The linearity of the proposed method is better than spectrophotometric methods and comparable to other fluorimetric methods. The proposed method is less precise and accurate as compared to a reported method [1] which involve the use of CdS QDs but the environment friendly nature of ZnS QDs as compared to CdS QDs outweigh this deficiency.…”
Section: Comparison Of the Proposed Methods With Reported Analytical Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…The linearity of the proposed method is better than spectrophotometric methods and comparable to other fluorimetric methods. The proposed method is less precise and accurate as compared to a reported method [1] which involve the use of CdS QDs but the environment friendly nature of ZnS QDs as compared to CdS QDs outweigh this deficiency.…”
Section: Comparison Of the Proposed Methods With Reported Analytical Methodsmentioning
confidence: 83%
“…Ciprofloxacin (Cf) is a synthetic, broad-spectrum, second-generation fluoroquinolone antibiotic that shows activity against both gram-positive and gram-negative bacteria [1] through inhibition of their DNA gyrase. It is used to treat various bacterial infections, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation coefficient of Langmuir isotherm (R 2 ) was 0.9992 which shows correlation or linear relationship, Thus, it was found that adsorption of CPH correlated well with the Langmuir equation. According to Equation (11), the adsorption constants of Langmuir isotherm model parameters, q max and K L , were obtained as 263.15mg/g and 0.0460L/mg, respectively.…”
Section: Langmuir Isothermmentioning
confidence: 99%
“…Many analytical methods have been developed to determine CIP residue in various food and environmental samples, such as spectrophotometry [ 5 , 6 , 7 ], capillary electrophoresis [ 8 ], and high-performance liquid chromatography using UV [ 9 ], fluorescence [ 10 , 11 ], diode array [ 12 ], and mass spectrometry [ 13 ]. For the instrumental analysis, sample pre-treatment is essential for the purification and enrichment of trace CIP residue in complex matrices.…”
Section: Introductionmentioning
confidence: 99%